Rattus norvegicus infectados com Trypanosoma cruzi : efeitos clínicos do tratamento com Lycopodium clavatun e Phosphorus ultradiluídos - Massini, Paula Fernanda (2013)
Chagas disease, caused by the protozoan Trypanosoma cruzi, is a disease typically tropical and widely dispersed in the Americas, representing a challenge to public health in Latin America. In Brazil, only benznidazole is available for the treatment of this condition and, besides having limited efficacy in chronic phase, also has high toxicity and significant adverse effects that reduce patient compliance to treatment. In this sense, the search for new therapeutic approaches more effective and less toxic has driven the study drug highly diluted, offering hope and benefit to patients with Chagas disease. Furthermore, studies using homeopathic medicines with controlled experiments and observations associated with experimental models toughest possible to obtain clinical information that offer best study conditions. This test consists of a paper in which we discuss the results of experiments with homeopathic medicines, Lycopodium clavatum (LY) and Phosphorus (PH), natural substances that have important biological effects in the treatment of Trypanosoma cruzi infection in wistar mice. Clinical parameters included weight, temperature, water consumption and diet, amount of excreta, heart rate and breathing, intestinal length and intestinal stenosis, aspects of fur and feces. The results showed that the use of chemotherapeutics derived from natural products, Lycopodium clavatum 13DH and Phosphorus, brought benefits to treated animals. The use of Lycopodium clavatum and Phosphorus and diluted 1:1x1026 showed beneficial effects different. Ten and five of 14 parameters analyzed showed positive effects for LY and PH, respectively. The parameters of water and feed consumption, amount of feces, diarrhea, drop by, heart rate and respiratory, intestinal length and showed a significant difference compared to control infected which reinforces the importance of further studies with T. cruzi versus drugs hight diluted